Time‐resolved small‐angle neutron scattering study on guest‐exchange processes in co‐crystals of syndiotactic polystyrene. (4th February 2014) - Kaneko, Fumitoshi; Radulescu, Aurel; Ute, Koichi
<x xml:space="preserve">Abstract</x> Syndiotactic polystyrene (sPS) occupies a peculiar position among crystalline polymers: it forms co‐crystals with many different kinds of chemical compounds, where the molecules are confined as guests in the regularly arranged cavities surrounded by the side phenyl groups. The guest molecules can be replaced smoothly by exposure to a vapour or a liquid of another compound, keeping the framework of the host polymer crystallites. It has been confirmed that the guest‐exchange procedure is an effective way to incorporate a variety of chemical species into the crystalline region of syndiotactic polystyrene. In order to elucidate its characteristics, the guest‐exchange process in co‐crystals of syndiotactic polystyrene has been studied by in situ time‐resolved small‐angle neutron scattering measurements, exploiting the scattering length difference between fully protonated and deuterated isotopologues of guest compounds and employing fully deuterated syndiotactic polystyrene as the host matrix to avoid strong incoherent scattering. In this study, the guest‐exchange process induced by exposure to the gas of small guest molecules was followed by monitoring of the reflections from crystalline lamellae. The lamellar reflections showed significant variations in intensity during the guest exchange, from which the diffusion coefficients of the guest molecules in the crystalline region could be evaluated.